Из истории журнальной периодики: журнал «Крым» (1925-1927 гг.) - Моисеенкова, Л.С.; Шарапа, В.Ф. (Материалы по археологии, истории и этнографии Таврии, 2000)
The authors examine the history of the creation of the magazine of Russian Society of Studying Crimea (RSOSC, РОПИК in Russian), which was published in Moscow in 1925 -1927. Only ten issues of the KRYM (Crimea) magazine were published. There were 5 sections in it. In the “General Information” sections 90 scientific articles and popular science essays on the history, geography, economy and culture of the Crimea were published. In the “Chronicle of RSOSC” section there was detailed information about the activity of the administration of the society and its Moscow and Leningrad branches. In the “Excursion" section they gave theory and practice of excursion business in the Crimea. In the “On the places” section they gave chronicles of the Crimean lore and social life. In the “Summaries and bibliography” section they published current bibliography of guidebooks, books, magazine articles about the Crimea. Various materials published in the magazine enable us to get an idea about the creation and activities of RSOSC. The KRYM magazine became a part of lore study of the 20s, its propagandist, and organizer and moving spirit.